2021
DOI: 10.1002/adfm.202104814
|View full text |Cite
|
Sign up to set email alerts
|

Viral Transduction Enhancing Effect of EF‐C Peptide Nanofibrils Is Mediated by Cellular Protrusions

Abstract: Self‐assembling peptide nanofibrils (PNF) have gained increasing attention as versatile molecules in material science and biomedicine. One important application of PNF is to enhance retroviral gene transfer, a technology that has been central for gene therapy approaches. The best‐investigated and commercially available PNF is derived from a 12‐mer peptide termed EF‐C. The mechanism of transduction enhancement depends on the polycationic surface of EF‐C PNF, which bind to the negatively charged membranes of vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…We observed that the interactions of peptides with cells and viruses are mostly driven by three codependent properties: (I) ordered structure (II) microscopic aggregation and (III) positive surface charge. While the importance of zeta-potential and fibril formation was already suggested for EF-C PNF in previous reports 12 , 26 , 55 , microscopic aggregation—which we found to correlate strongly with infectivity—was not systematically studied nor identified as a necessary feature before.…”
Section: Discussionmentioning
confidence: 64%
“…We observed that the interactions of peptides with cells and viruses are mostly driven by three codependent properties: (I) ordered structure (II) microscopic aggregation and (III) positive surface charge. While the importance of zeta-potential and fibril formation was already suggested for EF-C PNF in previous reports 12 , 26 , 55 , microscopic aggregation—which we found to correlate strongly with infectivity—was not systematically studied nor identified as a necessary feature before.…”
Section: Discussionmentioning
confidence: 64%
“…We observed that the interactions of peptides with cells and viruses are mostly driven by three codependent properties: (I) ordered structure (II) microscopic aggregation and (III) positive surface charge. While the importance of zeta-potential and fibril formation was already suggested for EF-C PNF in previous reports, [12,26,71] microscopic aggregation -which we found to correlate strongly with infectivity -was not systematically studied nor identified as a necessary feature before.…”
Section: Discussionmentioning
confidence: 67%
“…We hypothesize that µm-sized aggregates can accelerate infectivity by physical entanglement with cellular protrusions, which are actively transporting the fibril/virus complexes to the cell surface, where virions can enter the cells. [71] Interestingly, for aggregates larger than 10 µm 2 it is not the size, but rather the number of aggregates correlating with infectivity enhancement. Fibrils aggregating to few very large aggregates might simply not offer enough particles for virus-cell interactions or may be too big to get efficiently engaged by protrusions.…”
Section: Discussionmentioning
confidence: 99%
“…43 More recently it has also been shown that cellular protrusions actively engage EF-C fibril/virion complexes, suggesting that not only electrostatic interactions may account for bioactivity. 44 Our method demonstrates that moderately negatively charged peptide fibrils can be active if the hydrophobicity and aggregation features are both strongly pronounced. Hydrophobic amino acids such as tryptophan, phenylalanine, and cysteine can facilitate these desired properties; the continuous vector representation of peptides successfully extracts this underlying information by processing sequence and activity information of the training set.…”
Section: Discussionmentioning
confidence: 85%